Validity of E-module on Ion equilibrium and pH of salt solution oriented Chemo-Entrepreneurship (CEP) (International Journal of Scientific Research and Management (IJSRM), 2022)
The Covid-19 pandemic has affected many sectors of life, including education. Educators are required to be able to carry out online learning processes and design interesting learning instruments. One of them is a teaching material in form of E-module. In this study, the E-module was designed by utilizing a digital application, namely the kvisoft flipbook maker. The design of this e-module was oriented to chemo-entrepreneurship (CEP) on ion equilibrium and the pH of salt solution materials. The aim of this study was that students possessed the skills to make a chemical-based product. The validity of the E-module was carried out with the Plomp research design consist of an initial investigation phase, a design phase, a realization/construction phase, and a validation phase. The results of the validity of E-module oriented CEP on ion equilibrium and the pH of salt solution materials revealed that the validity from the material expert was 95% with valid category and the validity from the media expert was 87% with valid category.